EFFECTS OF DRUGS ABUSE ON ACADEMIC PERFORMANCES OF STUDENTS OF SULTAN ABDURRAHMAN SCHOOL OF HEALTH TECHNOLOGY, GWADABAWA - Malami Dikko; Murtala Malami; Abdullahi A. Sadiq; Ahmad Zayyanu (Journals Park Publishing, 2022)
This study examined the effects of drug abuse on the academic performances of students of Sultan Abdurrahman School of Health Technology Gwadabawa. The purpose of the study was to determine whether the students of the school use drugs of abuse to influence their academic performances. Research questionnaires were used to collect data from the students of both sexes. Distribution of respondents according to Demographic Characteristics shows that out of 354 respondents, 56% were males ad 44% were females, therefore, majority were males. It also shows that 56% of the respondents were between 18-24years, 28% were between 25-34years while 16% were above 35years, therefore, majority of respondents were between 18-24years. On whether students of Sultan Abdurrahaman School of Health Technology, Gwadabawa take illicit drugs in order to enhance their academic performances or not ? The result showed that out of 354 respondents, 30.8% agreed, 15.0% strongly agreed, 34.2% disagreed, and 19.9% strongly disagreed. On research question " Are illicit drugs available and accessible to the students of Sultan Abdurrahman School of Health Technology, Gwadabawa?" The result revealed that, out of 354 respondents, 32.8% agreed, 19.1% strongly agreed, 37.8% disagreed, and 10.2% strongly disagreed. On the research question " Are the male students of Sultan Abdurrahman School of Health Technology, Gwadabawa predominant drug abusers? the results revealed that out of 354 respondents, 28.8% agreed, 15.4% strongly agreed, 30.4% disagreed, and 25.4% strongly disagreed. Another research question "Does drug abuse increases the cases of indiscipline among the students of Sultan Abdurrahman School of Health Technology, Gwadabawa? Result shows that out of 354 respondents, 31.7% agreed, 15.9% strongly agreed, 37.6% disagreed, and 14.8% strongly disagreed. Conclusively, the study showed that the students of Sultan Abdurrahman School of Health Technology, Gwadabawa do not use illicit drugs since there was no availability and accessibility of such drugs to them. This means that drug abuse does not influence the academic performances of the students of Sultan Abdurrahman School of Health Technology, Gwadabawa.
Keywords: Health Technology; academic performances; Research